PENERAPAN ALGORITMA C4.5 UNTUK MEMPREDIKSI KELULUSAN SISWA DI SDN LEUWIRANJI 05 BERDASARKAN DATA HISTORIS - Wafiatul Khoiriyah Nasution; Mochamad Adhari Adiguna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The quality of education is highly dependent on the institution's ability to manage and analyze student data effectively. This study aims to apply the C4.5 algorithm in predicting student graduation at SDN Leuwiranji 05 based on historical data, such as average report card grades, number of absences (Alpha), and sick data. The methodology used refers to the CRISP-DM (Cross Industry Standard Process for Data Mining) model, starting from business understanding, data understanding, data preparation, modeling, evaluation, presentation. The described dataset consists of 108 student data with the results of 77 students graduating and 31 failing. The initial entropy calculation result is 0.8648, and the highest gain value is obtained from the